Eletrodeposição de filmes do tipo Ni-X (X=P, Cu ou Cu-P) a partir de banhos contendo aspartato - Brito, Matheus Macedo de (Universidade Federal de São Carlos, 2022)
In the present work, aspects related to the electrodeposition of Ni-based metal films - either pure metal or Ni-P, Ni-Cu, and Ni-Cu-P alloys - from baths containing aspartate complexes as electroactive species and hypophosphite anion as the source of phosphorus for the alloys containing this element were addressed. Stable solutions were obtained at pH 6.0, which allowed the formation of the desired codeposits, with the P content in the Ni-P alloy ranging from 15 to 22%, the Cu content in the Ni-Cu alloy ranging from 13 to 22%, while in the Ni-Cu-P alloy, the P content ranged from 1 to 3% and the Cu content was in the range of 24 to 43%, depending on the current density applied for electrodeposition. It was observed that the process efficiencies were affected by the presence of P and Cu, with the former leading to a decrease and the latter leading to an increase in this parameter. The morphology of the films that did not contain Cu was always smooth, with few or no grain boundaries visible by microscopy, while the alloys containing Cu showed the formation of dendritic structures on the electrode surface. Surface composition analysis revealed the presence of Ni(II) oxides in all samples, Cu(II) in Ni-Cu and Ni-Cu-P alloys, and, in the films containing P, the presence of oxidized P(III) and P(V) species were observed. The deposition condition of -60 mA cm-2 with a total load of 40 C cm-2 was selected to produce films for corrosion tests, with the Ni-P film showing superior corrosion resistance in NaCl medium than the Ni-Cu and Ni-Cu-P films, which are shown to be better than the Ni film. The higher corrosion resistance of the Ni-P film was correlated to the presence of surface Ni(II) and P(V) species, which act as a protective layer.
Electrodeposition of Ni-X (X=P, Cu or Cu-P) films from aspartate containing baths
Keywords: Eletroquímica; Eletrodeposição; Aspartato; Níquel; Cobre; Fósforo; Electrodeposition; Electrochemistry; Nickel; Copper; Phosphorus; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::CAMPOS DE COORDENACAO; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA